2014
DOI: 10.1097/nna.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Nursing Practice

Abstract: Data analysis revealed ethical duty to care, negative perceptions toward patients with substance abuse/dependence, need for further education, sympathy, and issues with pain management. Providing quality nursing care for the hospitalized medical-surgical patient with concomitant alcohol and/or drug dependence is challenging for nursing. Nurses need additional education and professional support in caring for these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 10 publications
2
32
1
1
Order By: Relevance
“…In our study, these existential feelings of aloneness were identified when the provided care became procedural and equivalent to actions predicted by the algorithm of the procedures, thus rendering the nurses not to see the particularity of the patient. The present study thus draws attention back to the fundamentals of nursing in terms of elucidating that there still is more to care than cure, which is much needed according to previous research within the area of patients suffering from AUD (Lovi & Barr, 2009;Neville & Roan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, these existential feelings of aloneness were identified when the provided care became procedural and equivalent to actions predicted by the algorithm of the procedures, thus rendering the nurses not to see the particularity of the patient. The present study thus draws attention back to the fundamentals of nursing in terms of elucidating that there still is more to care than cure, which is much needed according to previous research within the area of patients suffering from AUD (Lovi & Barr, 2009;Neville & Roan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Third, maternity nurses may need professional role support to overcome barriers to caring for pregnant and postpartum women with SUDs -especially barriers encountered in caring for women who do not fit the norm of the "good patient." Support from other nurses and inter-professional colleagues can help nurses confront any biases that interfere caring for patients with SUDs (Neville & Roan, 2014). Maternity nurses need opportunities to develop strategies to form trusting relationships with pregnant and postpartum women with SUDs and to improve the quality of care they provide for them and their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Det kan vaere veldig forvirrende.» (Vår oversettelse.) (19,22) Frykter å bli lurt «Sykepleiere opplevde å bli lurt når disse pasientene spurte om smertestillende.» Sykepleiere opplevde å bli lurt når disse pasientene spurte om smertestillende. Av sykepleierne mente 20,8 prosent at opioidavhengige forteller sannheten når de formidler smerte, mens 29 prosent av sykepleierne svarte at pasientene forsøker å lure dem når de spør om smertestillende (20).…”
Section: Mangler Kunnskapunclassified